Locally advanced breast cancer (LABC) and delayed care: a qualitative analysis of psychosocial factors. Issue 2 (7th February 2023) - Saita, Emanuela; Acquati, Chiara; Molgora, Sara; Vagnini, Denise; Piccolo, Eleonora Maria; Valenti, Francesco; Stratta, Gregorio; Grassi, Massimo Maria
ABSTRACT: The literature has extensively documented how delayed access to health care services in the context of cancer can result from subjective characteristics, dysfunctional coping styles, barriers to care, or procrastination. However, limited research has investigated the psychosocial experience of women diagnosed with Locally Advanced Breast Cancer (LABC). This qualitative study aimed at understanding cognitive, emotional and relational factors associated with delayed access to care and treatment decision-making. In-depth interviews with 14 Italian women were conducted. A thematic analysis of elementary contexts using T-LAB was used to identify the association between emerging clusters and participants' coping styles as measured by the Mini-MAC. Five clusters were identified: 'relationships', 'ineluctability', 'disease', 'surgery', and 'diagnosis' . The ' relationships ' cluster was characterized by elevated rates of Fighting Spirit ( p < 0.01) while Anxious Preoccupation was associated with 'surgery' ( p < 0.01). Findings contribute to explain individual and relational variables related to delay seeking care of LABC patients by illustrating the interplay of personal motivations and social networks' characteristics. Evidence from this work expands current understanding of the interplay of factors contributing to delays in seeking medical attention and may be utilized to inform strategies to timely identify women at greater risk.